2013
DOI: 10.1080/01140671.2013.801356
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the sugar import pathway into developing kiwifruit berries (Actinidia deliciosa)

Abstract: The aim of this work was to investigate the roles of the apoplasmic and symplasmic pathways in the delivery of solutes to the outer pericarp of developing green-fleshed kiwifruit berries (Actinidia deliciosa [A. Chev.] C. F. Liang et A. R. Ferguson var. deliciosa 'Hayward'). Experiments with the symplasmic tracer 5(6)-carboxyfluorescein (CF) showed symplasmic movement of dye during the initial rapid growth stage of the fruit, but as fruit growth slowed and starch content increased, a reduction in symplasmic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…At the same time, the main water transport pathway changes from xylem to phloem (Lang and Thorpe, 1989; Greenspan et al , 1996; Keller et al , 2015), and sugar transport shifts from the symplastic to apoplastic pathway (Zhang et al , 2006). Similar changes are observed in other fleshy fruits (Morandi et al , 2010; Clearwater et al , 2012; Gould et al , 2013; Brüggenwirth et al , 2016).…”
Section: Introductionsupporting
confidence: 83%
“…At the same time, the main water transport pathway changes from xylem to phloem (Lang and Thorpe, 1989; Greenspan et al , 1996; Keller et al , 2015), and sugar transport shifts from the symplastic to apoplastic pathway (Zhang et al , 2006). Similar changes are observed in other fleshy fruits (Morandi et al , 2010; Clearwater et al , 2012; Gould et al , 2013; Brüggenwirth et al , 2016).…”
Section: Introductionsupporting
confidence: 83%
“…2A , B , G , H ), were the dominant Suc-cleaving enzymes. The presence of symplasmic connectivity between phloem cells and vascular parenchyma cells ( Gould et al , 2013 ) and the lack of both cell wall invertase activity ( Moscatello et al , 2011 ) and the gene for a fruit-specific cell wall invertase (this study) in kiwifruit berries support this hypothesis. Tomato phloem unloading is still debated, and evidence supporting two contrasting theories has been produced using different systems.…”
Section: Discussionsupporting
confidence: 59%
“…For kiwifruit, Chen et al (2017) showed that sucrose phloem unloading occurs mainly through the apoplasmic route along fruit development (44–135 days after blooming). However, Gould et al (2013), working from 22 to 200 days after anthesis, found that phloem unloading dominantly appeared via symplasmic route in early fruit development, while an apoplasmic route becomes important during the later developmental stages. The dominant symplastic import of sugar at the initial stages of fruit development allows a high inflow of carbon input via mass flow.…”
Section: Phloem Loading and Unloading Strategies Differ Among Fruitsmentioning
confidence: 99%